Tackling per- and polyfluorinated alkyl substances in the North African Environment: Slight progress amidst significant challenges - Badreddine Barhoumi; Hassan Alshemmari; Abdulla M. Al-Rawabdeh; Lassaad Chouba; Mohamed Ridha Driss; Soufiane Touil; Philippe Bersuder; Imma Tolosa (Emerging Contaminants, 2025)
Per- and polyfluoroalkyl substances (PFAS) have attracted global attention due to their persistence, potential for bioaccumulation, and adverse effects on both human health and the environment. However, the extent and implications of PFAS contamination in North Africa remain insufficiently explored. This review addresses this regional knowledge gap by critically evaluating the occurrence, sources, and potential impacts of PFAS in environmental and human matrices across North Africa. Based on a comprehensive review of credible scientific sources, this analysis consolidates evidence of PFAS contamination across various environmental and human matrices. All examined matrices, including water, biota, air, foodstuffs, food packaging materials, and human samples, were contaminated by at least one PFAS compound. Potential sources of PFAS are discussed in relation to the known applications of specific compounds. Although PFAS levels reported in the North African environment are generally lower than those observed in more urbanized and industrialized countries, the findings clearly demonstrate the presence and widespread distribution of PFAS in the region. Notably, fish livers collected from Sudan exhibited the highest PFAS concentrations, with perfluorooctane sulfonic acid (PFOS) levels reaching up to 331 ng g−1 wet weight (ww), substantially exceeding the recommended Environmental Quality Standard (EQS) for PFOS in biota set at 9 ng g−1 ww. Identified sources of PFAS contamination include both industrial activities (e.g., manufacturing discharges, aqueous film-forming foams) and consumer-related sources (e.g., municipal landfills, electronic waste, port operations, and precursor degradation). Although toxicological assessments currently suggest a generally low risk to human and ecological health, this may be due to limited monitoring data rather than an actual absence of PFAS. Overall, this review enhances the regional understanding of PFAS pollution in North Africa, highlights critical data gaps, and outlines priorities for future research and policy development aimed at monitoring, regulating, and mitigating PFAS exposure in the region.